2020
DOI: 10.3389/fpls.2020.576718
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Regulation of Nitrogen and Sulfur on Redox Balance of Maize Leaves and Amino Acids Balance of Grains

Abstract: As a primary food crop, maize is widely grown around the world. However, the deficiency of essential amino acids, such as lysine, tryptophan, and methionine, results in poor nutritional quality of maize. In addition, the protein concentration of maize declines with the increase in yield, which further reduces the nutritional quality. Here, the photosynthesis of leaves, grain amino acid composition, and stoichiometry of N and S are explored. The results show that N and S maintained the redox balance by increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 82 publications
1
3
0
Order By: Relevance
“…Different nutrient composition and N release mechanisms in different SCU products may directly influence crop productivity. In our study, SCU contains 39% N and 13.8% sulphur, and there could be a synergistic effect of sulphur and nitrogen on cauliflower productivity, as reported in earlier studies (Liu et al, 2020;Rossini et al, 2018). Perveen et al (2021) reported that PCU in combination with sulphur fertilization increased sunflower yield by 32% over CU, without sulphur addition.…”
Section: Discussionsupporting
confidence: 87%
“…Different nutrient composition and N release mechanisms in different SCU products may directly influence crop productivity. In our study, SCU contains 39% N and 13.8% sulphur, and there could be a synergistic effect of sulphur and nitrogen on cauliflower productivity, as reported in earlier studies (Liu et al, 2020;Rossini et al, 2018). Perveen et al (2021) reported that PCU in combination with sulphur fertilization increased sunflower yield by 32% over CU, without sulphur addition.…”
Section: Discussionsupporting
confidence: 87%
“…No significant negative correlations with any of the nutrients were found. Various researchers have reported synergistic interactions between the N and S of different crop plants, which is mainly explained by the central role of S and N in protein synthesis [ 31 , 32 , 33 ]. In addition to N, a synergistic effect of S with P and K was also previously confirmed [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In plants, N is essential for protein formation, and any perturbation on its uptake and use will have metabolic consequences (Hawkesford et al., 2012). It has been shown that an adequate supply of N and S is relevant for an adequate redox balance in maize leaves (S. Liu et al., 2020). Higher glutamine synthetase protein levels in wheat were detected in WDS primed plants, indicating the importance of N metabolism under repeated WDS (X. Wang et al., 2014).…”
Section: Discussionmentioning
confidence: 99%